Human leptospirosis distribution pattern analysis in Hulu Langat, Selangor - Zulkifli, Z. (Institute of Physics Publishing, 2016)
This paper discussed the distribution pattern of human leptospirosis in the Hulu Langat District, Selangor, Malaysia. The data used in this study is leptospirosis cases' report, and spatial boundaries. Leptospirosis cases, data were collected from Health Office of Hulu Langat and spatial boundaries, including lot and district boundaries was collected from the Department of Mapping and Surveying Malaysia (JUPEM). A total of 599 leptospirosis cases were reported in 2013, and this data was mapped based on the addresses provided in the leptospirosis cases' report. This study uses three statistical methods to analyze the distribution pattern; Moran's I, average nearest neighborhood (ANN) and kernel density estimation. The analysis was used to determine the spatial distribution and the average distance of leptospirosis cases and located the hotspot locations. Using Moran's I analysis, results indicated the cases were random, with a value of -0.202816 which show negative spatial autocorrelation exist among leptospirosis cases. The ANN analysis result, indicated the cases are in cluster pattern, with value of the average nearest neighbor ratio is -21.80. And results also show the hotspots are has been identified and mapped in the Hulu Langat District.